The Cliffhangers: Suicide shows and the aesthetics of protest in China - Hillenbrand, M (Duke University Press, 2020)
Over the last couple of decades, workers in China’s vast and poorly regulated construction industry have increasingly turned to suicidal performance as a radical means of securing wage arrears. These so-called “suicide shows” have drawn attention as expressions of escalating labor unrest in China, and thus have mostly been read through a political science prism. But these displays, precisely in their dramatic dimension, also open themselves up to a culturalist, even aesthetic analysis: they braid together mixed threads, from the Chinese tradition of suicide as righteous remonstrance to present-day forms of creatively embodied protest in the era of Occupy. At the same time, though, these workers have also fashioned an aesthetic intervention which is very much of their own devising. This paper draws on an empirical base of two dozen suicide shows posted on video-sharing sites to argue that these performances force a visual rupture in the narcotically identikit Chinese cityscape, as the nation’s new poor, so often invisible to their social others on the street, climb to the highest urban summits and command extreme attention. Once there, they turn the rooftop into a site of performance which acts out the excruciating distinction between those who belong within the polis and the dispossessed: those who are cast out from the circle of humanity and are thus excluded from all avenues to legal and economic redress when they are wronged. As such, “cliffhanging” in China exemplifies what I call the fractious form, in which a tense encounter between different class actors under the regime of precarity becomes the genesis for a volatile cultural practice.